The Comparison of Maternal and Child Health Indicators before and after the Family Physician Program in Shiraz, from 2001 to 2012 - nasrin shokrpour; Roxana sharifian; mohaddese ghanbari jahromi; Mohammad khammarnia; aziz kasani (Shiraz University of Medical Sciences, 2017)
Introduction: One of the aims of the family physician program (FPP) is to improve the maternal and child health indicators. this study aimed to comparison maternal and child health indicators in Shiraz rural areas before and after implementation of FPP during 2001 to 2012. Methods: This applicable study was conducted in Shiraz in the south west of Iran in 2014. The child and maternal health indicators before (2001 to 2005) and after FPP (from 2006 to 2012) were gathered from the Health Center (Enghelab and Shohadaye Valfajr). The instrument for data collection was a questionnaire consisted of 20 maternal and child health indicators. Descriptive statistics was used and for analyzing the data, Excel and Stata software and comparisons of rates and joint point regression tests were employed. Results: the results showed that The FPP lead to decrease in stillbirth, infant mortality and child under one-year mortality in the rural area. Also all the vital horoscope indicator (mortality under one month, mortality under one year, the frequency of the infants under one year, the percentage of stillbirths, crude death percentage, crude birth percentage, general fertility percentage, total fertility percentage) have improved after FPP in Health Center rather than Enghelab Health Center . Conclusion: the maternal and child health indicators had improvement after FPP implementation. Therefore, it is recommended to continue the program.